Growth Activity of Apple Trees Depending on the Method and Timing of Crown Pruning - Chaploutskyi Andrii; Butsyk Roman; Chepurnyi Valery; Kucher Inna; Chetskyi Bohdan; Zabolotnyi Oleksandr (Journal of Horticultural Research, 2024)
The apple tree is one of the most widespread fruit crops in the world. As the area of plantings increases and horticulture transitions to intensive technologies, the demand for skilled workers increases. The introduction of mechanization processes can solve this problem at all stages of fruit production. The aim of this study was to investigate the effect of contour pruning and its modification at different times on the growth of ‘Jonaweld’ apple trees grafted onto the dwarf rootstock M.9 T337. As a result of contour pruning, the trunk diameter increased by 61% and the number of shoots by 40%. Contour pruning with manual refinement produced intermediate results between manual and contour pruning. Furthermore, contour pruning produced the shortest shoots, only 22 cm, compared to 29 cm with manual pruning. There was also a general tendency to limit the growth activity of trees due to postponing pruning. The growth of trunk diameter slowed by 25%, the number of shoots decreased by 8%, and their length decreased by 20%. Specific productivity was highest when contouring with postharvest refinement and pruning.